Dampak Media Sosial Terhadap Perubahan Struktur dan Kosakata Bahasa Indonesia di Kalangan Generasi Muda - anhar, Anhar; Muslimah, Nur Afifah Sarah; Nisa, Diva Icha; Fatimah, Nina (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Social media has become an integral part of the lives of young people, bringing a significant impact on the language they use daily. This study aims to analyze how social media affects changes in structure and vocabulary in Indonesian, as well as foreign language adaptations enrich or change language use among the younger generation. The type of research used is qualitative descriptive. Data were collected through semi-structured interviews with 30 participants selected using purosive sampling techniques. The data was analyzed thematically using N-Vivo qualitative analysis software. The results of the study show that there is a tendency to use foreign words, abbreviations, and new phrases that were previously uncommon in Indonesian. In addition, the sentence structure has also undergone adjustments, especially in the context of informal communication. These findings show that although social media provides flexibility in the use of language, there is a risk of deterioration in the quality of formal language if it is not balanced with a good understanding of standard Indonesian. This research is expected to provide insight for policymakers, educators, and the wider community about the need for language education that balances creativity with maintaining the integrity of the Indonesian language